Aksi Sehat Ramah Lingkungan: Edukasi dan Pembagian Sabun Cuci Tangan Berbahan Dasar Minyak Jelantah - Maulana, Ilham; Syari, Delviza; Angganawani, Rahmadhani Tyas; Yusup, Ahsan Maulana; Ananda, Lintang Tri; Shapira, Shari Bella; Ismiati, Silfia; Pratiwi, Vivi Amalia Dwi (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Used cooking oil is a household waste whose environmental and health impacts are often overlooked. Careless disposal can damage soil, water, and ecosystems. This community service aimed to educate the public about processing used cooking oil into environmentally friendly handwashing soap through a participatory-educational approach. Implemented by STIKes Bogor Husada at Sempur Field, Bogor City, as part of its 6th Anniversary, the activity involved direct outreach and distribution of soap made from used oil. A total of 100 bottles were distributed to more than 100 participants. The results showed increased understanding of the dangers of oil disposal and its economic potential if recycled. Positive responses, interest in further training, and wider impact through social media demonstrate that an educational approach with concrete actions is effective in fostering awareness and behavior, while serving as a contribution of higher education institutions in health advocacy and environmental sustainability.